The future of cancer nursing in Europe: Addressing professional issues in education, research, policy and practice - Drury Amanda; Sulosaari Virpi; Sharp Lena; Ullgren Helena; de Munter Johan; Oldenmenger Wendy (Elsevier, 2025)
Cancer nursing has evolved to meet the demands of rising cancer incidence, newer and more complex treatment options, and the emergence of specialist roles supporting patients from pre-diagnosis, through treatment, survivorship and end of life care. Nurses are involved in direct and in-direct care of people at risk of, and living with and after cancer in diverse contexts. As a result, nurses are positioned to have a significant influence on the processes and outcomes of cancer care, through education, research, policy, practice and leadership. However, nursing and cancer care face challenges, arising from workforce shortages, under-investment in services and under-representation in decision-making. This paper discusses the evolution of cancer nursing across education, policy, research, profession and practice, and sets an agenda for innovation and disruption across these domains to ensure sustainability of cancer care services and care for people living with and after cancer. We argue for the continued advancement of cancer nursing with critical focus on identifying and addressing inequities in role recognition and access to specialist cancer nursing education throughout Europe. Partnership, exchange of learning, and co-design will be central to progressing education, evidence and policy to support future growth in the cancer nursing workforce and embed cancer nurses in research and policy setting at local, national and international levels.